(untitled) (Global Journal of Medical Research, 2021)
I am the medical director and sole physician at a 35-bed nursing home in Western Galilee in Israel. At the end of December 2020, the nursing home experienced a COVID outbreak in which nineteen residents were infected. Four of them were symptomatic, and two died. Ten staff members, including our administrator, likewise caught the disease, and five of them were symptomatic. All recovered. The first part of this paper will examine why, despite all our precautions, the outbreak occurred when it did, and why it spread extensively within the home. The second part will describe how the nursing home functioned after the outbreak, until its residents recovered.